Applicability of riverbank filtration system in removing electrical contaminants from Sungai Belat using activated carbon: a laboratory testing - Nurhazirah, Abdul Malik (2014)
Demand of safe and and clean drinking water are increasing every day, especially in developing country such as Malaysia. High population will increase water demand proportionally but the supply of water is still low. Due to this concern, riverbank filtration system was implemented as an alternative to produce safe and clean drinking water in a faster and economical way. Common conventional water treatment process involve coagulation, flocculation, sedimentation, filtration and disinfection. Unlike conventional water treatment, riverbank filtration system in this study use riverbank soil modified with activated carbon (AC). Activated carbon is used as a medium of adsorption to remove all the organic contaminants found in water. Four parameters of water are taken into consideration in this study which are electrical conductivity, salinity, total dissolved solid and total hardness. These parameters will indicates the class of water. Sungai Belat water fall into the class II, which need further treatment for drinking water. Soil characteristic were also investigated to determine the type of soil of the riverbank in the area. The particle size distribution (sieve analysis and hydometer), Atterberg limit (liquid limit and plastic limit) and specific gravity were measured. Based on these test, the soil have 94 % of sand and 6 % clay. Adsorption test was conducted between different masses of soil and water using TDS as an indicator. The optimum time and mass (15 min with 2 g soil) was used in the adsorption test. This test will determine the most suitable ratio used for the filtration. 20:80 ratio was found to be the best ratio. Based on the filtration test, the filtration using natural soil with activated carbon was better than natural soil only. Three parameters which were electical conductivity, total dissolved soliad and hardness show decresing in value meanwhile salinity decreased. Further treatment should be carried out to achieve INWQS standard.